Cardiovascular and metabolic consequences of the association between chronic stress and high-fat diet in rats - Simas, Bruna B.; Nunes, Everson A.; Crestani, Carlos C. [UNESP]; Speretta, Guilherme F. (Taylor & Francis, 2018)
Obesity and chronic stress are considered independent risk factors for the development of cardiovascular diseases and changes in autonomic system activity. However, the cardiovascular consequences induced by the association between high-fat diet (HFD) and chronic stress are not fully understood. We hypothesized that the association between HFD and exposure to a chronic variable stress (CVS) protocol for four weeks might exacerbate the cardiovascular and metabolic disturbances in rats when compared to these factors singly. To test this hypothesis, male Wistar rats were divided into four groups: control-standard chow diet (SD; n = 8); control-HFD (n = 8); CVS-SD (n = 8); and CVS-HFD (n = 8). The CVS consisted of repeated exposure of the rats to different inescapable and unpredictable stressors (restraint tress; damp sawdust, cold, swim stress and light cycle inversion). We evaluated cardiovascular function, autonomic activity, dietary intake, adiposity and metabolism. The HFD increased body weight, adiposity and blood glucose concentration (∼15%) in both control and CVS rats. The CVS–HFD rats showed decreased insulin sensitivity (25%) compared to CVS–SD rats. The control-HFD and CVS–HFD rats presented increased intrinsic heart rate (HR) values (∼8%). CVS increased cardiac sympathetic activity (∼65%) in both SD- and HFD-fed rats. The HFD increased basal HR (∼10%). Blood pressure and baroreflex analyzes showed no differences among the experimental groups. In conclusion, the present data indicate absence of interaction on autonomic imbalance evoked by either CVS or HFD. Additionally, HFD increased HR and evoked metabolic disruptions which are independent of stress exposure.
Keywords: Adipose stores; autonomic activity; baroreflex activity; chronic variable stress; insulin resistance; intrinsic heart rate